A Review of the Methods for Predicting the Effective In-Plane Shear Modulus of Cross-Laminated Timber (CLT) - Mehsam Tanzim Khan; Ying Hei Chui; Dongsheng Huang (Advances in Civil Engineering)
Cross-laminated timber (CLT) is a type of engineered wood product that offers both high in-plane and out-of-plane load-bearing capacity. It is slowly becoming an alternative material for building high-rise structures. However, there is no current standard or regulation for determining the shear modulus of CLT under in-plane loading condition, which is a very important property for its use as structural members. Few methods have been proposed over the last decade to determine the in-plane shear modulus of CLT. Almost all of the methods proposed until now have their strengths and weaknesses. In this paper, some of the prominent methods for determining the in-plane shear modulus of CLT are described and analysed. The descriptions along with the critical discussions will facilitate a better understanding and might pave the way to further enhancements of the method(s) to determine the in-plane shear modulus of CLT.